Prevention of school stress - Valentin Martínez-Otero Pérez (INFAD, 2014)
The interest for child stress has increased during recent years. Previously it was thought that childhood was certainly a “happy period” and consequently it was ignored the possibility that children could suffer this psychological condition. Even nowadays, within the theoretical debate, there is not always an agreement about this illness. It is not easy to make a psychological diagnosis since the younger the children are, the more difficult is to find the stress symptoms as they differ greatly from the ones found in adults. This study is based in a previous research that aimed to find cases of child depression within the school population. Taking this research as a starting point, it was reviewed the relevant theoretical questions about the causes and consequences of stress during the childhood. At the same time the article reveal preventive measures to be applied mainly in schools.